Host and structure-specific codon usage of G genotype (VP7) among group A rotaviruses - Liu, Ziwei; Zhao, Simiao; Jin, Xinshun; Wen, Xiaobo; Ran, Xuhua (Frontiers in Veterinary Science, 2024)
Rotavirus A (RVA) infects a relatively wide host range. Studying the evolutionary dynamics of viral genomes and the evolution of host adaptations can inform the development of epidemiological models of disease transmission. Moreover, comprehending the adaptive evolution of viruses in the host could provide insights into how viruses promote evolutionary advantages on a larger scale at host level. This study aims to determine whether host specificity in codon usage existed. We used the Clustal W function within MEGA X software to perform sequence alignment, followed by construction of a phylogenetic tree based on the maximum-likelihood method. Additionally, Codon W software and EMBOSS were utilized for analysis of codon usage bias index. We analyzed codon usage bias (CUB) of host-specific G genotype VP7 to elucidate the molecular-dynamic evolutionary pattern and reveal the adaptive evolution of VP7 at the host level. The CUB of RV VP7 exhibits significant difference between human and other species. This bias can be primarily attributed to natural selection. In addition, the β-barrel structural domain, which plays a crucial role in viral transmembrane entry into cells, demonstrates a stronger CUB. Our results provide novel insights into the evolutionary dynamics of RVs, cross-species transmission, and virus-host adaptation.